Continuity & Transformation of Zapin Meskom Music in Bengkalis Regency - Zalfandri; Daryusti (Gondang: Jurnal Seni dan Budaya, 2026)
This study analyses the continuity and transformation of Zapin Meskom music in Bengkalis Regency, Riau, as a Malay cultural heritage amid modern social change. It aims to explain the tradition's forms of sustainability and the performance changes occurring in a contemporary context. The study uses a qualitative method with a descriptive-analytical approach. We gathered data through observation, in-depth interviews with artists, traditional leaders, and community members, and documentation studies. We analysed the data using the interactive model of Miles, Huberman, and Saldana: data reduction, data display, and conclusion drawing. The results show that Zapin Meskom's continuity rests on preserved core elements: basic movement patterns, the rhythms of gambus and marwas, Malay-language verses, and the values of courtesy and togetherness. Intergenerational transmission through families, art studios, and cultural communities supports this continuity. Transformation shows up in adjusted performance duration, modern stage arrangements, costume innovations, and the use of digital media and cultural festivals as new spaces of expression. Technological developments, tourism, cultural policy, and globalization drive these changes. Zapin Meskom demonstrates a dynamic relationship between tradition and modernity. Tradition preserves local cultural identity. Transformation works as an adaptation strategy that keeps the art relevant. Zapin Meskom continues to endure as a living, evolving cultural heritage in the Bengkalis community.